Framing of the news of sexual harassment cases that occurred in higher education in CNN Indonesia Online Media - Sheisa Ayu Saras Tungga (Enrichment : Journal of Management, 2023)
This research examines the reporting of cases of sexual harassment in tertiary institutions that occurred throughout 2021–2022. According to the 2022 Komnas Perempuan CATAHU, tertiary institutions occupy the first number of cases of violence in the educational environment based on education level, with a percentage of 35%. Using the Gamson and Modigliani framing analysis with the framing device and reasoning device, the results show that, first, CNN uses sentences that imply that students as victims of sexual harassment have difficulty seeking justice because of unequal power relations. Second, CNN is more on the victim's side and legitimizes that sexual harassment can be carried out verbally and physically by lecturers in various modes or by using their authority as teaching staff. Third, CNN has also added visual images in the form of infographics that explain sexual harassment and its types to make anyone aware that sexual harassment can happen anywhere and to anyone, including even in universities, and this needs to be watched out for. Overall, CNN uses a fair gender perspective in reporting sexual harassment in tertiary institutions by not cornering students as victims.